Home My Page Projects Code Snippets Project Openings diderot

# SCM Repository

[diderot] Diff of /branches/charisee/src/compiler/high-il/normalize-ein.sml
 [diderot] / branches / charisee / src / compiler / high-il / normalize-ein.sml

# Diff of /branches/charisee/src/compiler/high-il/normalize-ein.sml

revision 2602, Wed Apr 23 20:01:52 2014 UTC revision 2603, Thu Apr 24 03:58:37 2014 UTC
# Line 4  Line 4
4      local      local
5
6      structure E = Ein      structure E = Ein
7      structure P=Printer(*      structure P=Printer
8      structure O =OrderEin*)      structure F=Filter
9        structure G=EpsHelpers
10      in      in
11
12    fun err str=raise Fail (String.concat["Ill-formed EIN Operator",str])
(*Flattens Add constructor: change, expression *)
|flatten(i,((E.Const c):: l'))=
if (c>0 orelse c<0) then let
val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end
else flatten(1,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let
val(b,a)=flatten(i,l') in (b,[e]@a) end

val (b,a)=flatten(0,e)
in case a
of [] => (1,E.Const(1))
| [e] => (1,e)
(* end case *)
end

fun mkProd [e]=(1,e)
| mkProd(e)=let
fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')
|flatten(i,((E.Const c)::l'))=
if(c>0 orelse  0>c) then (3,[E.Const 0])
else flatten(i,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let val(a,b)=flatten(i,l') in (a,[e]@b) end
val (change,a)=flatten(0,e)
in if(change=3) then (1,E.Const(0))
else case a
of [] => (1,E.Const(0))
| [e] => (1,e)
| es => (change, E.Prod es)
(* end case *)
end

13
14
(* filter function shifts constant/greeks to outside product*)
fun filter2([],pre,eps,dels,post)=(pre,eps,dels,post)
| filter2(E.Const c::es,pre, eps,dels,post)=filter2(es, pre@[E.Const c],eps,dels,post)
| filter2(E.Delta d::es,pre,eps,dels,post)= filter2(es,pre,eps,dels@[E.Delta d],post)
| filter2(E.Value v::es, pre, eps,dels,post)=filter2(es, pre@[E.Value v],eps,dels,post)
| filter2(E.Epsilon e::es, pre,eps,dels, post)=filter2(es, pre,eps@[E.Epsilon e],dels,post)
| filter2(E.Tensor(id,[])::es, pre,eps, dels,post)=filter2(es, pre@[E.Tensor(id,[])],eps,dels,post)
| filter2(E.Prod p::es, pre,eps,dels, post)=filter2(p@es,pre,eps,dels,post)
| filter2(e::es, pre,eps,dels, post)= filter2(es, pre, eps,dels,post@[e])

(*Only used to find eps, and embedded sums*)
fun findeps(e,(E.Epsilon eps)::es,rest)=  findeps(e@[E.Epsilon eps],es,rest)
| findeps(e, E.Sum(sx,E.Prod(E.Epsilon eps::ps))::es,rest)= (e@[E.Epsilon eps], rest@ps@es,sx)
| findeps(e, E.Prod p::es,rest)=findeps(e, p@es,rest)
| findeps(e, E.Field f::es,rest)=findeps(e, es,rest@[E.Field f])
| findeps(e, E.Tensor t::es,rest)=findeps(e, es,rest@[E.Tensor t])
| findeps(e,es,rest)= (e, rest@es,[])

15
16
17  fun prodAppPartial ([e1],p1)= E.Apply(E.Partial p1,e1)  fun prodAppPartial ([e1],p1)= E.Apply(E.Partial p1,e1)
18    | prodAppPartial((e1::e2),p1)=let    | prodAppPartial((e1::e2),p1)=let
19      val l= prodAppPartial(e2,p1)      val l= prodAppPartial(e2,p1)
20      val (_,e2')= mkProd[e1,l]      val (_,e2')= F.mkProd[e1,l]
21      val (_,e1')=mkProd(e2@ [E.Apply(E.Partial p1, e1)])      val (_,e1')=F.mkProd(e2@ [E.Apply(E.Partial p1, e1)])
22      in      in
24      end      end
25
26
27    (*rewritten Sum*)
28    fun mkSum(c1,e1)=(case e1
29  (*remove eps Index*)      of E.Conv _   => (0,E.Sum(c1,e1))
30        | E.Field _   => (0,E.Sum(c1,e1))
31  fun rmEpsIndex(i,[],[],[])= []      | E.Probe _   => (0,E.Sum(c1,e1))
32      | rmEpsIndex(i,[],x,[])= [x]      | E.Apply _   => (0,E.Sum(c1,e1))
33      | rmEpsIndex(i,[],x,e::es)= rmEpsIndex(i,e,[],es)@[x]      | E.Delta _   => (0,E.Sum(c1,e1))
34      | rmEpsIndex(i,  ( c ,lb, ub)::b,x, es)=      | E.Epsilon _ => (0,E.Sum(c1,e1))
35          if (i=c) then let      | E.Tensor _  => (0,E.Sum(c1,e1))
36                  val z=[(x@b)]      | E.Neg e2    => (1,E.Neg(E.Sum(c1,e2)))
37                  in (case z of [] => es |_=>z@es) end      | E.Lift e    => (1,E.Lift(E.Sum(c1,e)))
38          else rmEpsIndex(i,b,x@[(c ,lb, ub)],es)      | E.Sum(c2,e2)=> (1,E.Sum(c1@c2,e2))
39        | E.Sub (a,b) => (1,E.Sub(E.Sum(c1,a),E.Sum(c1,b)))
40        | E.Div (a,b) => (1,E.Div(E.Sum(c1,a),E.Sum(c1,b)))
42  fun doubleEps(count,E.Epsilon (a,b,c),E.Epsilon(d,e,f))=let      | E.Prod p     =>F.filterSca(c1,p)
43      (*Function is called when eps are being changed to deltas*)      | E.Const _   => err("Sum of Const")
44      fun createDeltas(i,s,t,u,v)= let      | E.Partial _ => err("Sum of Partial")
45          val c'= rmEpsIndex(E.V i,[],[],count)      | E.Krn _     => err("Krn used before expand")
46          val d1=[E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)]      | E.Value _   => err("Value used before expand")
47          val d2= [E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]      | E.Img _     => err("Probe used before expand")
48        (*end case*))
49          in (1,c',d1,d2)
50          end  (*rewritten Apply*)
51    fun mkapply(d1,e1)=(case e1
52      in if(a=d) then createDeltas(a,b,c,e,f)      of E.Lift e   => (1,E.Const 0)
53          else if(a=e) then createDeltas(a,b,c,f,d)      | E.Prod []   => err("Apply of empty product")
54          else if(a=f) then createDeltas(a,b,c,d,e)      | E.Add []    => err("Apply of empty Addition")
55          else if(b=d) then createDeltas(b,c,a,e,f)      | E.Conv(v, alpha, h, d2)    =>let
56          else if(b=e) then createDeltas(b,c,a,f,d)                          val E.Partial d3=d1
57          else if(b=f) then createDeltas(b,c,a,d,e)                          in (1,E.Conv(v,alpha,h,d2@d3)) end
58          else if(c=d) then createDeltas(c,a,b,e,f)      | E.Field _   => (0,E.Apply(d1,e1))
59          else if(c=e) then createDeltas(c,a,b,f,d)      | E.Probe _   => (0,E.Apply(d1,e1))
60          else if(c=f) then createDeltas(c,a,b,d,e)      | E.Apply(E.Partial d2,e2)  => let
61          else (0,[],[],[])                          val E.Partial d3=d1
62      end                          in (1,E.Apply(E.Partial(d3@d2),e2)) end
63        | E.Neg e2    => (1,E.Neg(E.Apply(d1,e2)))
64        | E.Sum(c2,e2)=> (1,E.Sum(c2,E.Apply(d1,e2)))
66  fun distEps([],eps,_,_)=(0,[],[],[],[])      | E.Sub (a,b) => (1,E.Sub(E.Apply(d1,a),E.Apply(d1,b)))
67      | distEps([e],eps,_,_)=(0,[],[],[],[])      | E.Div (a,b) => (1,E.Div(E.Apply(d1,a),E.Apply(d1,b)))
68      | distEps(e1::e2::[],eps,c1::count,sx)=let      | E.Prod p =>let
69          val(change,c',d1,d2)= doubleEps([c1@sx]@count,e1,e2)          val (pre, post)= F.filterField p
70          in (case change          val E.Partial d3=d1
71          of 1=>(1, c', eps, d1,d2)          in F.mkProd(pre@[prodAppPartial(post,d3)])
72          |_=> (0,[],[],[],[])          end
73          (*end case*))      | E.Const _   => err("Const without Lift")
74          end      | E.Tensor _  => err("Tensor without Lift")
75        | E.Delta _   => err("Apply of Delta")
76      | distEps(e1::e2::current,eps,count,sx)=let      | E.Epsilon _ => err("Apply of Eps")
77          val(change,c',d1,d2)= doubleEps(count,e1,e2)      | E.Partial _ => err("Apply of Partial")
78          in (case change      | E.Krn _     => err("Krn used before expand")
79              of 1=>(1, c', eps@current, d1,d2)      | E.Value _   => err("Value used before expand")
80              |_=> distEps(e2::current, eps@[e1],count,sx)      | E.Img _     => err("Probe used before expand")
81              (*end case*))      (*end case*))
82          end
83
84    (*rewritten probe*)
85    fun mkprobe(e1,x)=(case e1
86  (* Transform eps to deltas*)      of E.Lift e   => (1,e)
87  fun epsToDels(count,E.Prod e)= let      | E.Prod []   => err("Probe of empty product")
88      val (epsA,es,sx)=findeps([],e,[])      | E.Prod p    => (1,E.Prod (List.map (fn(a)=>E.Probe(a,x)) p))
89      val (change, s', eps,d1,d2)= distEps(epsA,[],count,sx)      | E.Apply _   => (0,E.Probe(e1,x))
90      val deltas=E.Sub(E.Prod d1,E.Prod d2)      | E.Conv _    => (0,E.Probe(e1,x))
91        | E.Field _   => (0,E.Probe(e1,x))
92      in (case (change,eps,es)      | E.Add e     => (1,E.Add (List.map (fn(a)=>E.Probe(a,x)) e))
93          of (0,_,_)=>(print "nooo";(0,[],epsA,es))      | E.Sum(c,e') => (1,E.Sum(c,E.Probe(e',x)))
94          |(_,[],[]) =>(1,s',[deltas],[])      | E.Div (a,b) => (1,E.Div(E.Probe(a,x),E.Probe(b,x)))
95          | _ =>(1,s',[E.Sub( E.Prod(eps@d1@es), E.Prod(eps@d2@es))],[])      | E.Sub (a,b) => (1,E.Sub(E.Probe(a,x),E.Probe(b,x)))
96          (*end case *))      | E.Neg e'    => (1,E.Neg(E.Probe(e',x)))
97      end      | E.Const _   => err("Const without Lift")
98        | E.Tensor _  => err("Tensor without Lift")
99  (*Another strategy. Go through entire expression inside summation and jsut examine index to apply deltas*)      | E.Delta _   => err("Probe of Delta")
100        | E.Epsilon _ => err("Probe of Eps")
101  (* Apply deltas to tensors/fields*)      | E.Partial _ => err("Probe Partial")
102  fun reduceDelta(c, eps, dels, es)=let      | E.Probe _   => err("Probe of a Probe")
103      fun distribute(change,d,dels,[],done)=(change,dels@d,done)      | E.Krn _     => err("Krn used before expand")
104          | distribute(change,[],[],e,done)=(change,[],done@e)      | E.Value _   => err("Value used before expand")
105          | distribute(change,[],dels,e::es,done)=distribute(change,dels,[],es,done@[e])      | E.Img _     => err("Probe used before expand")
| distribute(change,E.Delta(i,j)::ds,dels,e::es,done)=(case e
of  E.Tensor(id,[tx])=>
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)
|  E.Field(id,[tx])=>
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)
| E.Apply(E.Partial d,e)=>let
fun distPart([],rest) =(0 ,rest)
| distPart(p::pd,rest)=
if(p=j) then (1,rest@[i]@pd)
else (distPart(pd,rest@[p]))
val (change'',p')=distPart(d,[])
in (case change''
of 0=>distribute(change, ds,dels@[E.Delta(i,j)], [E.Apply(E.Partial d, e)]@es,done)
|_=> distribute(change@[j], dels@ds,[], es,done@[E.Apply(E.Partial p', e)])
106                      (*end case*))                      (*end case*))
end
| _=>distribute(change,dels@[E.Delta(i,j)]@ds,[],es,done@[e])
(*end case*))

val (change,dels',done)=distribute([],dels,[],es,[])
fun m([],c')=c'
| m(e::es,c')= let val s=rmEpsIndex(e,[],[],c')
in m(es, s) end
val index= m(change, c)
in
(length change, index,E.Prod (eps@dels'@done))
end

107
108
109
(*Apply*)
fun mkApply(E.Apply(E.Partial d,e))=(case e
of E.Tensor(a,[])=>(1,E.Const 0)
| E.Const _ =>(1,E.Const 0)
| E.Delta _ =>(1,E.Const 0)
| E.Value _ =>(1,E.Const 0)
| E.Epsilon _ =>(1,E.Const 0)
| E.Conv (fid,alpha,tid, delta)=> (1, E.Conv(fid,alpha, tid, delta@d))
| E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, e)) l))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, e2), E.Apply(E.Partial d, e3)))
| E.Div(e2, e3) =>(1, E.Div(E.Apply(E.Partial d, e2),  e3))(********FIXX******)
| E.Apply(E.Partial d2,e2)=>(1,E.Apply(E.Partial(d@d2), e2))
| E.Prod [e1]=>(1,E.Apply(E.Partial d,e1))
| E.Prod es=> let
val (pre,eps,dels, post)= filter2(es,[],[],[],[])
val (_,x)=mkProd(pre@eps@dels@[prodAppPartial(post,d)])
in (1,x) end
|_=>(0,E.Apply(E.Partial d,e))
(* end case*))

(*Sum Apply*)

fun matchEps(2,_,_,_)= 1 (*matched 2*)
| matchEps(num,_,_,[])=0
| matchEps(0,_,_,[eps])=0
| matchEps(num,[],rest,eps::epsx)=
matchEps(num,rest,[],epsx)
| matchEps(num,E.V p::px,rest,eps::epsx)=
if(p=eps) then (matchEps(num+1,rest@px,[],epsx))
else matchEps(num,px,rest@[E.V p], eps::epsx)
| matchEps(num,p::px,rest,eps)=
matchEps(num,px,rest,eps)

(*

fun epsapply(c,eps,dels,post)=let
fun  applyEps(change,count,[],[],rest,done)= (print "kkk";(0,E.Const 0))
| applyEps(change,count,eps,epsrest,[],done)=(print "yyyy";(0,E.Const 0))
| applyEps(change,count,[],epsrest,r::rest,done)=(print "bb";applyEps(change,count,epsrest,[],rest,done@[r]))
| applyEps(change,count,eps1::eps,epsrest,r::rest,done)=( print "lrr";(case (r,eps1)
of (E.Sum(c2,E.Prod(E.Epsilon eps2::s2)),_)=> let
val (change', s',_,d1,d2)= distEps([eps1,E.Epsilon eps2],[],count@c2)
in (case change'
of 1=> let
val (_,p1)=mkProd(epsrest@eps@d1@dels@done@s2@rest)
val (_,p2)=mkProd(epsrest@eps@d2@dels@done@s2@rest)
in
(1,E.Sum(s',E.Sub(p1,p2))) end
| _=>applyEps(change,count,eps, epsrest@[eps1],r::rest,done)
(*end case*))
end
| (E.Conv(v,vx, h ,d),E.Epsilon(i,j,k))=> let
val change'= matchEps(0,d,[],[i,j,k])
in (case change' of 1=>  (1,E.Const 0)
|_=>  applyEps(0,count,epsrest@[eps1],[],rest,done@[r]))
end
|_=>applyEps(0,count,epsrest@[eps1],[],rest,done@[r])
(*end case*)))

val (change, s', eps',d1,d2)= distEps(eps,[],c)
in (case change
of 1 =>  let
val (_,p1)=mkProd(eps'@d1@dels@post)
val (_,p2)=mkProd(eps'@d2@dels@post)
in  (print "in changed";(1,E.Sub(E.Sum(s',p1), E.Sum(s',p2)))) end
|_=> (print "in apply eps";applyEps(0,c,eps,[],post,[]))
(*end case*))
end

*)

110   (*print summation range*)   (*print summation range*)
111  fun handleIndex e= (case e  fun handleIndex e= (case e
112      of E.C(cx)=> String.concat["'",Int.toString(cx),"'"]      of E.C(cx)=> String.concat["'",Int.toString(cx),"'"]
113      |  E.V(ix)=> Int.toString(ix)      |  E.V(ix)=> Int.toString(ix)
114  )      (*end case *))
115
116  fun handleSumRange (mu,lb,ub)= print(String.concat[(handleIndex mu),"[",Int.toString(lb),"-",Int.toString(ub),"]"])  fun handleSumRange (mu,lb,ub)= print(String.concat[(handleIndex mu),"[",Int.toString(lb),"-",Int.toString(ub),"]"])
117  fun printSx e=(print "\n \$";List.map handleSumRange e; print "\$")  fun printSx e=(print "\n \$";List.map handleSumRange e; print "\$")
118
# Line 291  Line 132
132                | E.Tensor _ =>body                | E.Tensor _ =>body
133                | E.Field _=> body                | E.Field _=> body
134                | E.Delta _ => body                | E.Delta _ => body
| E.Value _ =>body
135                | E.Epsilon _=>body                | E.Epsilon _=>body
136                | E.Conv _=>body                | E.Conv _=>body
137                  | E.Partial _=>body
138                  | E.Krn _ =>raise Fail"Krn before Expand"
139                  | E.Img _ => raise Fail"Img before Expand"
140                  | E.Value _=> raise Fail"Value before Expand"
141
142                    (*************Algebraic Rewrites **************)
143                | E.Neg(E.Neg e)=> rewriteBody e                | E.Neg(E.Neg e)=> rewriteBody e
144                | E.Neg e => E.Neg(rewriteBody e)                | E.Neg e => E.Neg(rewriteBody e)
145                | E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)                | E.Lift e => E.Lift(rewriteBody e)
147                     in if (change=1) then ( changed:=true;body') else body' end                     in if (change=1) then ( changed:=true;body') else body' end
148                | E.Sub(a, E.Field f)=> (changed:=true;E.Add[a, E.Neg(E.Field(f))])                | E.Sub(a, E.Field f)=> (changed:=true;E.Add[a, E.Neg(E.Field(f))])
# Line 308  Line 154
154                | E.Div(E.Div(a,b),c)=> rewriteBody (E.Div(a, E.Prod[b,c]))                | E.Div(E.Div(a,b),c)=> rewriteBody (E.Div(a, E.Prod[b,c]))
155                | E.Div(a,E.Div(b,c))=>  rewriteBody (E.Div(E.Prod[a,c],b))                | E.Div(a,E.Div(b,c))=>  rewriteBody (E.Div(E.Prod[a,c],b))
156                  | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)                  | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)
| E.Partial _=>body
| E.Krn(tid,deltas,pos)=> E.Krn(tid,deltas, (rewriteBody pos))
| E.Img(fid,alpha,pos)=> E.Img(fid,alpha, (List.map rewriteBody pos))
157
158                    (**************Apply, Sum, Probe**************)
159                  | E.Apply(E.Partial [],e)=> e
160                  | E.Apply(E.Partial d1, e1)=>let
161                    val e2 = rewriteBody e1
162                    val (c,e3)=mkapply(E.Partial d1,e2)
163                    in (case c of 1=>(changed:=true;e3)| _ =>e3 (*end case*))
164                    end
165                  | E.Apply(E.Prod e1,e2)=>E.Apply(E.Partial(F.filterPartial e1), rewriteBody e2)
166                  | E.Sum([],e)=> (changed:=true;rewriteBody e)
167                  | E.Sum(c,e)=>let
168                    val ref x=sumIndex
169                    val c'=[c]@x
170                    val e'=(sumIndex:=c';rewriteBody e)
171                    val ref s=sumIndex
172                    val z=hd(s)
173                    val (cng,e2)=(sumIndex:=tl(s);mkSum(z,e'))
174                    in (case cng
175                        of 1=> (changed:=true;e2)
176                        |_=> e2
177                        (*end case*))
178                    end
179                  | E.Probe(u,v)=>  let
180                    val (c',b')=mkprobe(rewriteBody u,rewriteBody v)
181                    in (case c'
182                        of 1=> (changed:=true;b')
183                        |_=> b'
184                        (*end case*))
185                    end
186
187                  (*************Product**************)                  (*************Product**************)
188                | E.Prod [e1] => rewriteBody e1                | E.Prod [e1] => rewriteBody e1
# Line 326  Line 197
197                | E.Prod(e1::E.Sub(e2,e3)::e4)=>                | E.Prod(e1::E.Sub(e2,e3)::e4)=>
198                  (changed :=true; E.Sub(E.Prod([e1,e2]@e4), E.Prod([e1,e3]@e4 )))                  (changed :=true; E.Sub(E.Prod([e1,e2]@e4), E.Prod([e1,e3]@e4 )))
199
| E.Prod [E.Partial r1,E.Partial r2]=>
(changed:=true;E.Partial(r1@r2))
| E.Prod(E.Partial r1::E.Partial r2::p)=>
(changed:=true;E.Prod([E.Partial(r1@r2)]@p))
200
201
202                  (*************Product EPS **************)                  (*************Product EPS **************)
203
204                  (* Apply (d, e) shoudl be convereted to Conv operator *)                  (* Apply (d, e) shoudl be convereted to Conv operator *)
205                | E.Prod(E.Epsilon(i,j,k)::E.Apply(E.Partial d,e)::es)=>let                | E.Prod(E.Epsilon(i,j,k)::E.Apply(E.Partial d,e)::es)=>let
206                   val change= matchEps(0,d,[],[i,j,k])                   val change= G.matchEps(0,d,[],[i,j,k])
207                   in case (change,es)                   in case (change,es)
208                  of (1,_) =>(changed:=true; E.Const 0)                  of (1,_) =>(changed:=true; E.Const 0)
209                      | (_,[]) =>E.Prod[E.Epsilon(i,j,k),rewriteBody (E.Apply(E.Partial d,e))]                      | (_,[]) =>E.Prod[E.Epsilon(i,j,k),rewriteBody (E.Apply(E.Partial d,e))]
210                      |(_,_)=> let                      |(_,_)=> let
211                          val a=rewriteBody(E.Prod([E.Apply(E.Partial d,e)]@ es))                          val a=rewriteBody(E.Prod([E.Apply(E.Partial d,e)]@ es))
212                          val (_,b)=mkProd [E.Epsilon(i,j,k),a]                          val (_,b)=F.mkProd [E.Epsilon(i,j,k),a]
213                          in b end                          in b end
214                  end                  end
215                | E.Prod(E.Epsilon(i,j,k)::E.Conv(V,alpha, h, d)::es)=>let                | E.Prod(E.Epsilon(i,j,k)::E.Conv(V,alpha, h, d)::es)=>let
216
217                  val change= matchEps(0,d,[],[i,j,k])                  val change= G.matchEps(0,d,[],[i,j,k])
218                  in case (change,es)                  in case (change,es)
219                      of (1,_) =>(changed:=true; E.Const 0)                      of (1,_) =>(changed:=true; E.Const 0)
220                      | (_,[]) =>E.Prod[E.Epsilon(i,j,k),E.Conv(V,alpha, h, d)]                      | (_,[]) =>E.Prod[E.Epsilon(i,j,k),E.Conv(V,alpha, h, d)]
221                      | (_,_) =>let                      | (_,_) =>let
222                          val a=rewriteBody(E.Prod([E.Conv(V,alpha, h, d)]@ es))                          val a=rewriteBody(E.Prod([E.Conv(V,alpha, h, d)]@ es))
223                          val (_,b) = mkProd [E.Epsilon(i,j,k),a]                          val (_,b) = F.mkProd [E.Epsilon(i,j,k),a]
224                          in b end                          in b end
225                  end                  end
226
# Line 367  Line 234
234                  let                  let
235
236                  val ref x=sumIndex                  val ref x=sumIndex
237                  val (i,s',e,rest)=epsToDels(x,body)                  val (i,s',e,rest)=G.epsToDels(x,body)
238                  in (case (i, e,rest)                  in (case (i, e,rest)
239                  of (1,[e1],_) =>(changed:=true;sumIndex:=s';e1)                  of (1,[e1],_) =>(changed:=true;sumIndex:=s';e1)
240                      |(0,eps,[])=>body                      |(0,eps,[])=>body
241                      |(0,eps,rest)=> let                      | _ => let
242                          val p'=rewriteBody(E.Prod rest)                          val p'=rewriteBody(E.Prod rest)
243                          val p''= (case p' of E.Prod p=>p |e=>[e])                          val p''= (case p' of E.Prod p=>p |e=>[e])
244                          val(_,b)= mkProd (eps@p'')                          val(_,b)= F.mkProd (e@p'')
245                          in b end                          in b end
246                          (*end case*))                          (*end case*))
247                   end                   end
# Line 385  Line 252
252                  val m= Kt x                  val m= Kt x
253
254                  val c'= [c1@c2]@x                  val c'= [c1@c2]@x
255                  val (i,s',e,rest)=epsToDels(c', E.Prod([E.Epsilon e1, E.Epsilon e2]@es1@es2@es))                  val (i,s',e,rest)=G.epsToDels(c', E.Prod([E.Epsilon e1, E.Epsilon e2]@es1@es2@es))
256                   val gsg=Kt s'                   val gsg=Kt s'
257
258
# Line 397  Line 264
264                      | _=>let                      | _=>let
265                          val eA=rewriteBody(E.Sum(c1,E.Prod(E.Epsilon e1::es1)))                          val eA=rewriteBody(E.Sum(c1,E.Prod(E.Epsilon e1::es1)))
266                          val eB=rewriteBody(E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es))                          val eB=rewriteBody(E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es))
267                          val (_,e)=mkProd([eA,eB])                          val (_,e)=F.mkProd([eA,eB])
268                          in e                          in e
269                          end                          end
270                      (*end case*))                      (*end case*))
271                  end                  end
272
273              | E.Prod(E.Delta d::es)=>let              | E.Prod(E.Delta d::es)=>let
274                  val (pre',eps, dels,post)= filter2(E.Delta d::es,[],[],[],[])                  val (pre',eps, dels,post)= F.filterGreek(E.Delta d::es)
275                  val ref x=sumIndex                  val ref x=sumIndex
276                  val (change,i',a)=reduceDelta(x, eps, dels, post)                  val (change,i',a)=G.reduceDelta(x, eps, dels, post)
277
278                  in (case (change,a)                  in (case (change,a)
279                      of (0, _)=> E.Prod [E.Delta d,rewriteBody(E.Prod es)]                      of (0, _)=> E.Prod [E.Delta d,rewriteBody(E.Prod es)]
280                      | (_, E.Prod p)=>let                      | (_, E.Prod p)=>let
281                          val (_, p') = mkProd p                          val (_, p') = F.mkProd p
282                          in (changed:=true;sumIndex:=i';p') end                          in (changed:=true;sumIndex:=i';p') end
283                      | _ => (changed:=true;sumIndex:=i';a )                      | _ => (changed:=true;sumIndex:=i';a )
284                      (*end case*))                      (*end case*))
285                      end                      end
286
287                | E.Prod[e1,e2]=> let val (_,b)=mkProd[rewriteBody e1, rewriteBody e2] in b end                | E.Prod[e1,e2]=> let val (_,b)=F.mkProd[rewriteBody e1, rewriteBody e2] in b end
288                | E.Prod(e::es)=>let                | E.Prod(e::es)=>let
289                      val e'=rewriteBody e                      val e'=rewriteBody e
290                      val e2=rewriteBody(E.Prod es)                      val e2=rewriteBody(E.Prod es)
291                      val(_,b)=(case e2                      val(_,b)=(case e2
292                          of E.Prod p'=> mkProd([e']@p')                          of E.Prod p'=> F.mkProd([e']@p')
293                          |_=>mkProd [e',e2])                          |_=>F.mkProd [e',e2])
294                  in b                  in b
295                     end                     end
(**************Apply**************)
296
(* Apply, Sum*)
| E.Apply(E.Partial d,E.Sum (c,e))=> let
val ref x=sumIndex
val x'=[c]@x
val e' = (sumIndex:=x';rewriteBody(E.Apply(E.Partial d, e)))
val ref s=sumIndex
in
(sumIndex:=tl(s);E.Sum(hd(s), e'))
end

| E.Apply(E.Partial [],e)=> e
| E.Apply(E.Partial p,E.Probe(E.Conv(fid,alpha,tid,d),x))=>
(changed:=true;E.Probe(E.Conv(fid,alpha,tid,d@p),x))
| E.Apply(E.Partial p,E.Conv(fid,alpha,tid,d))=>
(changed:=true;E.Conv(fid,alpha,tid,d@p))
| E.Apply(E.Partial p, e)=>let
val body'=E.Apply(E.Partial p, rewriteBody e)
val (c, e')=mkApply(body')
in (case c
of 1=>(changed:=true;e')
| _ =>e') end
| E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)

(************** Sum *****************)
| E.Sum([],e)=> (changed:=true;rewriteBody e)
| E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
| E.Sum(c, E.Sum(c', e))=> (changed:=true; E.Sum(c@c', e))
| E.Sum(c, E.Sub(e1,e2))=>(changed:=true; E.Sub(E.Sum(c,e1), E.Sum(c, e2)))
| E.Sum(c,E.Div(e1,e2))=>(changed:=true; E.Div(E.Sum(c,e1),E.Sum(c,e2)))
| E.Sum(c, E.Prod(E.Const e::es))=>(changed:=true;E.Prod[E.Const e,E.Sum(c, E.Prod es)])
| E.Sum(c, E.Prod(E.Value v::es))=>(changed:=true; E.Prod [E.Value v, E.Sum(c, E.Prod es)])
| E.Sum(c, E.Prod(E.Tensor(id,[])::es))=> (changed:=true;E.Prod [E.Tensor(id,[]), E.Sum(c, E.Prod es)])

| E.Sum(c,E.Prod e)=> let
val e' =rewriteBody(E.Prod e)
(*val _=print (String.concat["\n change \n",P.printbody(body ),"\n ==>\n",P.printbody(E.Sum(c,e')),"\n"])*)
val b'= (case e'
of E.Prod p=>let
val (_,b)=mkProd p
in b end
|_=>e'
(* end case*))
val _ =print(P.printbody( b'))
in E.Sum(c,b')
end
| E.Sum(c,e)=>let

val ref x=sumIndex
val c'=[c]@x

val A= Kt c'
val e'=(sumIndex:=c';rewriteBody e)
val ref s=sumIndex

val C= Kt s
val z=hd(s)

val B= Kt [z]
val D=Kt (tl(s))
in (sumIndex:=tl(s);E.Sum(z, e')) end

(*******************Probe*****************)
| E.Probe(E.Sum(c,s),x)=>(changed:=true;E.Sum(c,E.Probe(s,x)))
| E.Probe(E.Tensor t,_)=> E.Tensor t
| E.Probe(E.Neg e1,x)=>(changed:=true;E.Neg(E.Probe(e1,x)))
| E.Probe(E.Sub (a,b),x)=>
(changed:=true;E.Sub(rewriteBody(E.Probe(a,x)), rewriteBody(E.Probe(b,x))))
| E.Probe(E.Div (a,b),x) =>
(changed:=true;E.Div(rewriteBody(E.Probe(a, x)),b))
| E.Probe(E.Prod p, x)=>let
val _=print ("\n probe of prod \n ")
val (p',x')= (rewriteBody (E.Prod p), rewriteBody x)
fun  probeprod([],[e1]) =e1
| probeprod([],rest) = E.Prod rest
| probeprod(E.Const c::es,rest)=
(changed:=true;probeprod(es,rest@[E.Const c]))
| probeprod(E.Tensor t::es,rest)=
(changed:=true;probeprod(es,rest@[E.Tensor t]))
| probeprod(E.Krn e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Krn e]))
| probeprod(E.Delta e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Delta e]))
| probeprod(E.Value e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Value e]))
| probeprod(E.Epsilon e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Epsilon e]))
| probeprod(E.Partial e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Partial e]))
| probeprod(E.Field f::es,rest)=
(changed:=true;print "\n \$#\$ Found Field";probeprod(es,rest@[E.Probe(E.Field f, x')]))

(*  (changed:=true;E.Prod(rest@[E.Probe(E.Field f, x')] @es))*)
| probeprod(E.Conv f::es,rest)=
(changed:=true;print "\n \$#\$ Found Field";probeprod(es,rest@[E.Probe(E.Conv f, x')]))

(*(changed:=true;E.Prod(rest@[E.Probe(E.Conv f, x')] @es))*)
| probeprod(E.Prod p::es , rest)=
(changed:=true;probeprod(p@es,rest))
| probeprod(E.Sum(c,e)::es, rest)=
(changed:=true;print "\n \$#\$ Found Sum in probe product \n "  ;probeprod(es,rest@[E.Sum(c,E.Probe(e, x'))]))
| probeprod(E.Neg(e)::es, rest)=
(changed:=true;probeprod(es,rest@[E.Neg(E.Probe(e, x'))]))
| probeprod(_,[])=body
| probeprod(e1::es, rest)=let
val e'= rewriteBody(E.Prod(e1::es))
val e''= rewriteBody(E.Probe(e',x'))
in  (changed:=true;E.Prod(rest@[e'']))
end
in (case p'
of E.Prod pro=>probeprod(p,[])
|_=> E.Probe(p',x')
(*end case*))
end
| E.Probe(u,v)=>  (E.Probe(rewriteBody u, rewriteBody v))
297              (*end case*))              (*end case*))
298
299              fun loop(body ,count) = let              fun loop(body ,count) = let
# Line 552  Line 301
301
302                             in                             in
303                if !changed                if !changed
304                  then (print(String.concat["\n=>",P.printbody(body')]);                  then (print(String.concat["\nN =>",Int.toString(count),"--",P.printbody(body')]);
305                  changed := false ;sumIndex:=[];loop(body',count+1))                  changed := false ;sumIndex:=[];loop(body',count+1))
306                  else (body',count)                  else (body',count)
307              end              end

Legend:
 Removed from v.2602 changed lines Added in v.2603